Ẩn danh

Giải hệ phương trình: \(\left\{{}\begin{matrix}\dfrac{3}{x}+\dfrac{\sqrt{y-2}}{2}=4\\\dfrac{4}{x}-3\sqrt{y-2}=-2\end{matrix}\right.\)

 

Akai Haruma
6 tháng 5 lúc 0:32

Lời giải:
Đặt $\frac{1}{x}=a; \sqrt{y-2}=b$ thì HPT trở thành:

\(\left\{\begin{matrix} 3a+\frac{1}{2}b=4\\ 4a-3b=-2\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} 18a+3b=24\\ 4a-3b=-2\end{matrix}\right.\)

$\Rightarrow (18a+3b)+(4a-3b)=24+(-2)$

$\Leftrightarrow 22a=22\Leftrightarrow a=1$

$b=(4a+2):3=(4.1+2):3=2$

Vậy: \(\left\{\begin{matrix} a=1\\ b=2\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} \frac{1}{x}=1\\ \sqrt{y-2}=2\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} x=1\\ y=6\end{matrix}\right.\)

Bình luận (0)

Các câu hỏi tương tự
Kiều Phương Phạm
Xem chi tiết
Kim Tuyền
Xem chi tiết
Nott mee
Xem chi tiết
Nguyễn Minh Anh
Xem chi tiết
Dung Vu
Xem chi tiết
Ahihi
Xem chi tiết
Rhider
Xem chi tiết
DŨNG
Xem chi tiết
Miko
Xem chi tiết
ILoveMath
Xem chi tiết